2020
DOI: 10.1002/adma.202003264
|View full text |Cite
|
Sign up to set email alerts
|

Zeolite (In)Stability under Aqueous or Steaming Conditions

Abstract: zeolites, modification of zeolite acidity for use as fluid catalytic cracking (FCC) catalysts or even for the preparation of novel zeolite frameworks. [1] Considering the significance of zeolite applications at the industrial level, a thorough understanding of zeolite (in)stability under aqueous conditions has been identified as a very important problem in catalysis and zeolite science. Zeolite (in)stability in water or under steaming conditions has been investigated by a number of experimental techniques, in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
125
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 94 publications
(141 citation statements)
references
References 267 publications
(342 reference statements)
7
125
0
Order By: Relevance
“…Similar vicinal mechanisms have been reported earlier for aluminosilicate zeolites by Malola et al, 17,52 albeit with much higher reaction barriers when forming either vicinal disilanols or vicinal aluminol and silanol pairs. From the vicinal product, the hydrolysis can proceed via the standard equatorialinversion mechanism (Figure S14b), but the overall effective barriers (70 kJ/mol) are lower and the reaction energies (-49 kJ/mol) more favorable than in Ge-poor UTL.…”
Section: Ge-rich Utlsupporting
confidence: 85%
See 2 more Smart Citations
“…Similar vicinal mechanisms have been reported earlier for aluminosilicate zeolites by Malola et al, 17,52 albeit with much higher reaction barriers when forming either vicinal disilanols or vicinal aluminol and silanol pairs. From the vicinal product, the hydrolysis can proceed via the standard equatorialinversion mechanism (Figure S14b), but the overall effective barriers (70 kJ/mol) are lower and the reaction energies (-49 kJ/mol) more favorable than in Ge-poor UTL.…”
Section: Ge-rich Utlsupporting
confidence: 85%
“…We analyzed the mechanism of Ge-O bond hydrolysis for three different locations of Ge atoms, always considering all four adjacent framework oxygen atoms (Figure S12). Hydrolysis starts via an equatorial step (Figure 4), as previously described in the literature for the hydrolysis of Si-O bonds, 17,[48][49][50][51] with reaction barriers of at least 65 kJ/mol. The reaction product is an unstable Q 3 Ge species (Figure 5).…”
Section: Ge-poor Utlmentioning
confidence: 89%
See 1 more Smart Citation
“…It was suggested that this process could aid the regeneration (de-coking) of the zeolite during de-NO x conversion. The reactivity of zeolites with H 2 O (both in liquid or gaseous form) has long been of interest, as it has important implications for the structural integrity of these systems in a variety of industrial processes 112. In recent work using17 O NMR spectroscopy39,40 the synthesis of new zeolites via the ADOR 40,41 process was investigated.…”
mentioning
confidence: 99%
“…12,13 The ADOR process exploits labile Ge-rich double-four ring (D4R) units in germanosilicates, such as UTL or *CTH. 14,15 The structure of these zeolites consists of Si-rich layers connected by Ge-rich D4Rs. Upon selective hydrolysis of D4Rs, layered materials are formed, thus preserving their original structure.…”
Section: Introductionmentioning
confidence: 99%